Erlotinib Associated Trichomegaly in a Patient with Chronic Latanoprost Use - Burris CK; Richards NQ; Cowan CL Jr (Journal of Hematology and Oncology Research, 2015)
Trichomegaly is a known adverse effect with the epidermal growth factor receptor inhibitor (EGFRI) and prostaglandin analogue drug classes. We present a chronic Latanoprost user who developed symptomatic trichomegaly subsequent to initiating an EGFRI medication and believe this case offers evidence that the two classes of medications may cause a similar eyelash manifestation through different mechanisms.
Keywords: Trichomegaly